Ternate Historical Site as an Object Based Education for Sustainable Development - Suswandari Suswandari (STKIP Singkawang, 2017)
This study aims to classify the historical sites of Ternate based on the timeliness of its existence. This study uses a critical qualitative historical approach and is conducted in several locations related to the history of Ternate. Data relating to the physical facts of Ternate history sites, then the location of research in the Ternate region of North Maluku. Data were collected from several findings and poured in filed notes. Then do the sorting and grouping to found description. Data were analyzed using critical historical analysis techniques. The Ternate history sites identified in this research consist of Ternate Museum of Ternate, Ternate Great Mosque, Kastela Fortress, Toluko Fortress, Kalamata Fortress, Oranje Bull, and Nala Fortress. Seven sites are conditions vary and still require government intervention to be used as an object of tourism which can then become an economic power for the people of Ternate. With the Education For Sustainable Development (EDS) approach, historical site development takes care of the needs and involves the community directly with full results for the benefit of the people of Ternate and the wider Indonesian community.